The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.20944/preprints202108.0443.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Welding of Copper to Aluminium With Laser Beam Wavelength of 515 nm

Abstract: In laser joining of copper (Cu) and aluminum (Al) sheets, the Al sheet is widely chosen as the top surface for laser irradiation because of increased absorption of laser beam and lower melting temperature of Al in contrast to Cu. This research focus on welding from Cu side to Al sheet. The main objective of irradiating the laser beam from the copper side (Cu on top) is to exploit higher solubility of Al in Cu. A significantly lower laser power can be used with 515 nm laser in comparison to 1030 nm. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…The distribution of these phases with a combination of ductile and brittle intermetallic structures apparently was achieved with parameter set #5, as the average tensile strength of this parameter set was found to be the highest for the oscillating welds. This outcome confirms the studies in [ 49 ], where this type of oscillation is also found to be beneficial for the distributing of the intermetallic phases, since the fluid flow and the resulting fusion zone follow the trajectory of the laser beam. For the linear stitched weld, a higher maximum tensile load could be achieved in case of #2 with lower line energy.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The distribution of these phases with a combination of ductile and brittle intermetallic structures apparently was achieved with parameter set #5, as the average tensile strength of this parameter set was found to be the highest for the oscillating welds. This outcome confirms the studies in [ 49 ], where this type of oscillation is also found to be beneficial for the distributing of the intermetallic phases, since the fluid flow and the resulting fusion zone follow the trajectory of the laser beam. For the linear stitched weld, a higher maximum tensile load could be achieved in case of #2 with lower line energy.…”
Section: Resultssupporting
confidence: 90%
“…Studies in this direction, using visible wavelengths such as green and blue, are currently less comprehensive in the literature [ 48 ]. Mathivanan et al [ 49 ] investigated the mechanical properties of copper aluminum welds in overlap configuration using a beam oscillation in the form of infinite shape with 515 nm laser radiation. A discontinuous weld seam was observed in cross-sectional direction, which was related to the different degree of intermixing.…”
Section: State Of the Artmentioning
confidence: 99%
See 2 more Smart Citations
“…Fig 28. Cross-sectional view of Cu-Al joint with schematic and micrograph showing the failure location after tensile shear test49) …”
mentioning
confidence: 99%